THE PROCEDURE AND THE EFFECTIVENESS TOWARDS DISPUTE REGISTRATIONS USING E-COURT SERVICES AT BATAM RELIGIOUS COURT 1-A CLASS - Luthfia Hidayah; Rahmi Ayunda (Universitas Internasional Batam, 2022)
Rapid technological developments have brought changes, especially in the judiciary. Online case registration are using e-court services in which its services is issued by the Supreme Court in accordance with the provisions of Supreme Court Regulation Number 3 of 2018 Regarding of Cases Administration. The purpose of establishing an e-court is to realize the principles of justice in a simple, fast, and low-cost manner. Besides being able to do case registration online, e-courts are capable to summon litigants online get an up-front assessment of court fees directly, pay down-payment fees online by getting a SKUM (payment statement letter) and a Virtual Account Bank. The purpose of writing this article is to find out how to register a divorce lawsuit using e-court services within the Religious Courts and find out what obstacles occur when registering cases through e-court services. The implementation method used by the author is normative juridical with the identification of problems that occur in a comprehensive integrative manner, the data analysis used is qualitative analysis with secondary data studies. The results of this study will show how the procedure for registering cases through e-court services at the Religious Courts Batam Class 1-A